2021
DOI: 10.1194/jlr.tr120000972
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipids as critical players in retinal physiology and pathology

Abstract: Sphingolipids have emerged as bioactive lipids involved in the regulation of many physiological and pathological processes. In the retina, they have been established to participate in numerous processes, such as neuronal survival and death, proliferation and migration of neuronal and vascular cells, inflammation, and neovascularization. Dysregulation of sphingolipids is, therefore, crucial in the onset and progression of retinal diseases. This review examines the involvement of sphingolipids in retinal physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 354 publications
1
33
0
Order By: Relevance
“…The overall role of sphingolipid metabolism in the retina is discussed in detail by Simon et al . in this issue ( 103 ).…”
Section: Potential Retinal-specific Mechanisms: What We Can Learn Fromentioning
confidence: 87%
“…The overall role of sphingolipid metabolism in the retina is discussed in detail by Simon et al . in this issue ( 103 ).…”
Section: Potential Retinal-specific Mechanisms: What We Can Learn Fromentioning
confidence: 87%
“…Additionally, there were four sphingolipids that were negatively associated with AUDAC. Given the role of sphingolipids in signaling pathways, multiple studies have suggested sphingolipids have a crucial role in the progression of AMD through the mediation of proliferation, survival, migration, neovascularization, inflammation, and death in retina cells [ 54 , 55 , 56 , 57 ]. As these sphingolipids were associated with AUDAC, and not RIT, it may suggest AUDAC may be a more sensitive functional measurement than RIT in measuring AMD progression due to its ability to measure DA beyond the 20 min ceiling for RIT.…”
Section: Discussionmentioning
confidence: 99%
“…Ceramide is a bioactive lipid that regulates a wide array of cellular processes [ 108 ]. Studies on animal models of diverse retinal diseases including retinitis pigmentosa, glaucoma, diabetic retinopathy, retinal ischemia, light-induced retinal degeneration, Stargardt disease, and AMD have identified ceramide as a mediator of pathology [ 42 , 43 , 109 , 110 ]. In these models, increased ceramide has been shown to promote injury, inflammation and death in photoreceptors, the RPE, and the retinal vasculature.…”
Section: Genetic Tipping Points and Novel Therapeutic Targets For Amdmentioning
confidence: 99%
“…Decreasing ceramide levels either pharmacologically or by genetic deletion of ASM has been shown to prevent retinal degeneration in several of these models [ 43 , 109 , 111 ]. These studies suggest that ceramide levels need to be tightly regulated in the retina, and any disruptions to the sphingolipid rheostat can have severe consequences for retinal health and function (recently reviewed in [ 110 ]).…”
Section: Genetic Tipping Points and Novel Therapeutic Targets For Amdmentioning
confidence: 99%